Calculation of Mobility on Combined Mechanisms Based on the Modified G-K's Formula - Xu Zhaotang (Jixie chuandong)
Using the modified Grübler-Kutzbach's formula of mechanism mobility, the calculation of the mobility of combined mechanism may produce wrong results. In order to correctly calculate the mobility of combined mechanism, and to consider that the calculation method of the mobility of combined mechanism is convenient for engineers for study and application, according to the modified Grübler-Kutzbach's formula of the mechanism mobility, the calculation formula of mobility of combined mechanism is deduced. The general calculation formula of mobility of mechanism is obtained. The attentions of calculating mobility of combined mechanism are proposed. The method of dividing the combined mechanism into basic mechanisms is given. Numerical examples are given. The modified Grübler-Kutzbach's formula of mechanism mobility can only be used to calculate mobility of a basic mechanism, and to calculate mobility of combined mechanism in that each basic mechanism has the same common constraint. The mobility of general combined mechanism should be calculated by the calculation formula of mobility of combined mechanism. The mobility of combined mechanism is equal to the sum of the mobility of each basic mechanism.